Pendekatan fungsional-struktural dalam adat pernikahan Sunda - Mujianto Mujianto (Jurnal Linguistik Terapan, 2016)
There is some argument about the conception of culture. Broadly culture is the daily life of human beings in general scale, ranging from action to thinking. Another opinion, culture is a set of rules, recipes, plan, and instructions used by humans to regulate behavior. In other words, culture is all activities undertaken by humans, including how, step, means, each of which function in order to meet its needs. The implication, if culture is conceived of all activities undertaken by humans that serve to meet the needs, understanding or cultural assessment can be done with a functional-structural approach. This is because the structural-functional approach is based on the assumption that every culture has a structure consisting of various elements or an element of life and each element or elements have the function of mutual support to cultural integrity. To understand more about the functional-structural approach, the following will be described on the conception of the functional-structural approach and its application in the study of traditional Sundanese wedding.